Effect of truncal vagotomy and/or pyloroplasty on gallbladder amptying and plasma CCK in humans - Mahir ÖZMEN,; Mükerrem ÇETE,; RS PATANKAR,; A. SANDERSON,; CD JOHNSON, (Turkish Journal of Gastroenterology, 2019)
-